Virtual clinical excursions-general hospital : for medical-surgical nursing:concepts and practice - DeWit, Susan C.; Cooper, Kim [ (Kim D.)] (Elsevier Saunders, 2013)
Presents a CD-ROM/workbook package that helps bridge the gap between the classroom and the real world by introducing you to clinical settings and critical thinking before you actually start clinical rotations - making the transition from nursing student to caregiver a smoother process